The Effectiveness of Nurse-Led Outreach Programs for At-Risk Populations: A Comprehensive Review of Patient Education Outcomes and Nursing Interventions - Kaabi, Najla Rizq Saad; Bejawi, Najat Medany Alaraby; Alosaimy , Refah Mohamad Bedah; YAHYA , NAIF IBRAHIM; Misawa , Gharam Abdulrahman Aqeel; Masawi , Maram Abdurahman AQEEL; Alzahrani , Ibtehal Musaed; ALOTAIBI, NAWAF ABDULLAH MOHAMMAD; Alshaikh, Aisha Abdu Qassim; Al Moabadi, Amer Mohamad; Alotaibl, NUJUD MUHANNA Almuzalnl; Alotaibi, Amal Shari Abdulrahman; et al. (Journal of Ecohumanism, 2024)
Background: Nurse-led clinics (NLCs) have emerged as a pivotal innovation in healthcare, aiming to enhance the management of chronic diseases while ensuring patient-centric care. However, the effectiveness of these clinics in promoting patient education and health outcomes remains inadequately evaluated, particularly regarding standardized nursing terminologies. Methods: This review systematically examined the literature on nurse-led outreach programs for at-risk populations, focusing on the outcomes of patient instruction based on the Nursing Outcome Classification (NOC). A comprehensive search of electronic databases, including Medline, Embase, and Web of Science, was conducted to identify relevant studies published up to 2023. Results: The findings indicate that NLCs significantly improve patient outcomes, particularly in managing chronic conditions such as hypertension and diabetes. Standardized nursing languages were found to enhance the assessment of educational outcomes, enabling nurses to evaluate the effectiveness of their interventions more accurately. Additionally, the review highlighted the importance of addressing psychological health outcomes alongside physical health metrics. Conclusion: The integration of evidence-based practices in nurse-led outreach programs is essential for optimizing patient education and health outcomes. This study underscores the necessity for further research to systematically evaluate the impact of NLCs on diverse patient populations and to develop effective educational strategies that can be standardized across healthcare settings